The Gettier Problem: An Analysis in the Context of al-Fārābī’s Epistemic Levels - Muhammed Abdullah Haksever (İslam Tetkikleri Dergisi)
In the history of philosophy, knowledge has been defined in the traditional sense since Plato as justified true belief. Despite the dominance of this definition in epistemology, the adequacy of the fundamental elements that make up definitive knowledge has been opposed and questioned. One of those who oppose the definition is Edmund L. Gettier (d. 2021), and the issue he posed known as the Gettier Problem, which is one of the most serious objections to the Platonic definition of knowledge. Gettier attempted to prove his idea that justified true belief could not create knowledge in people, asserting that some elements of luck could also contribute. Gettier showed that some wrong justifications can lead to a proposition that is actually true. In this sense, he expressed through examples that the components that constitute knowledge such as justification, truth, and belief, are insufficient. Meanwhile, Fârâbî (d. 339/950) showed in his works that it is possible to reach precise knowledge, especially in his Şerâʾiṭu’l-yaḳîn. As a matter of fact, the concept that Fârâbî used for certain knowledge is certitude (yakîn), and that the epistemic level of knowledge is formed and the degree of certainty can be determined to the extent that the elements constituting the knowledge are fulfilled. In this regard, yakîn in the context of justified true belief constitutes the highest epistemic level. This study aimed to analyze the problem that Gettier attempted to prove in terms of Fârâbî’s perception. Among the elements of certain knowledge is the epistemic luck factor, which Gettier draws attention to, which was examined in what way it had a position in Fârâbî’s philosophy and how it is taken out of the definition. Based on this, the claims and criticisms put forward by Gettier were examined to determine where Fârâbî falls within Gettier’s understanding of knowledge. Also, Gettier’s objections to the Platonic definition of knowledge were determined through Fârâbî’s understanding of yakîn.